Caracterização dinâmica e estática no Édipo Tirano de Sófocles - Colonnelli, Marco Valério Classe (2015)
This thesis addresses two conceptions of characterization in the play “Oedipus Tyrannus” of Sophocles. The first conception of characterization was extracted from the poetics of Aristotle. From the Poetic, we collected facts on the concept of character (ἦθος), along with all the implications that it is associated with. The same concept, by the inadequacy of the Poetic text, was compared with other statements from the Rhetoric and from The Nicomachean Ethics so that we could clarify certain main passages in the definition of the concept. The first conception of characterization we call dynamic characterization. Regarding the second conception of characterization, we started from Aristotle, going through other modern authors including: Tomachevsky, Robert Scholes, De Termemann, among others, so we could not only demonstrate the limits of Aristotelian characterization, but also seize another phenomenon of characterization in the epic and tragic works of authors, such as Homer, Aeschylus, Sophocles and Euripides. The second conception of characterization we term as static characterization. In the third part of the thesis, we undertook an analysis of the characters of Oedipus, on the Sophocles play, based on the theory proposed in the two theoretical chapters. Finally, based on the analysis, we demonstrate the insufficiency of the Aristotelian theory of characterization in relation to the potentialities of the tragic genre, addressing the complex structure in which Sophocles built the piece and the characterization of his character.